IMPACT OF RISK APPETITE ON THE VALUE OF A FIRM - Epetimehin, Festus M (European Scientific Journal, ESJ, 2013)
In order to strike the appropriate balance between creating and protecting value, management considers an overall risk profile in order develop expectations that are established by the risk appetite of the company. Risk appetite as acceptable parameters for risk taking opportunities that is consistent throughout the company, and reflects a mutual understanding between management’s willingness to allow risk exposure in pursuit of core strategic objectives. Conversely, managers see risk appetite as an impractical, one-time assessment that limits them when making decisions. Making use of secondary data collected through library research, journals and analysis of reports, the paper reviewed the impact of risk appetite on the value of a firm and concluded that an organization must consider its risk appetite at the same time decides which goals or operational tactics to pursue. To determine risk appetite, management, should take three steps of developing risk appetite, communicate risk appetite, monitor and update risk appetite.﻿